Programming interviews exposed : secrets to landing your next job - Mongan, John, 1976-; Suojanen, Noah, 1978-; Giguère, Eric, 1967- (Wrox professional guides., 2013)
Be prepared for your next job interview with this tried-and-true adviceProgramming Interviews Exposed.